Effect of Xenia on popping characteristics in popcorn - Santacruz-Varela, Amalio; de la O Olán, Micaela; Alegría-Hernández, Faustino Hugo; Ortega-Paczka, Rafael; López-Sánchez, Higinio; Sangerman-Jarquín, Dora Ma. (Revista Mexicana de Ciencias Agrícolas, 2022)
In the process of genetic fertilization of corn (Zea mays L.), pollen exerts a direct and immediate effect on the properties of the resulting caryopsis known as Xenia. This situation is of great importance in popcorn, since the popping capacity depends directly on the characteristics of the endosperm, so it is necessary to study the magnitude of Xenia in popcorns to give appropriate recommendations for the production and conservation of this genetic resource. The present study was carried out in 2018, the effect of Xenia of corn varieties of different endosperm constitution was evaluated on physical and popping characteristics of the caryopsis of two genotypes of popcorn. The experiment was conducted in two localities, Montecillo, State of Mexico and Santa María Zacatepec, municipality of Juan C. Bonilla, Puebla, using a randomized complete block experimental design. The varieties of popcorn Compuesto Amarillo and North American Yellow Pearl Popcorn were used as female parents, while the same materials, CML-349 of semicrystalline endosperm and a population of the Cacahuacintle race of mealy endosperm were used as male parents. The results showed that Compuesto Amarillo had a decrease in the dimensions of the caryopsis from 0.17 to 13%, while in NAYPP, the effect resulted in an increase, from 2.27 to 18%. The popping volume showed the greatest effect of Xenia, since in Compuesto Amarillo, it decreased from 25 to 49% when pollinated with non-popcorns, while in NAYPP the decrease was 59%. According to the results, there was an effect of Xenia on the popcorn evaluated, which was greater on the volume of expansion, while in the physical characteristics of the caryopsis, this effect was less pronounced.